2011
DOI: 10.1007/s00384-011-1135-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of percutaneous abscess drainage on severe postoperative septic complications in patients with Crohn's disease

Abstract: PAD of intra-abdominal abscesses before surgery could significantly reduce the occurrence of severe postoperative IASC in patients with CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 17 publications
2
31
1
2
Order By: Relevance
“…PAD has become a widely accepted treatment for accessible postoperative abscesses [9][10][11][12][13]. However, antimicrobial therapy is another important element of the management of intraabdominal infections.…”
Section: Introductionmentioning
confidence: 99%
“…PAD has become a widely accepted treatment for accessible postoperative abscesses [9][10][11][12][13]. However, antimicrobial therapy is another important element of the management of intraabdominal infections.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients (33%-50%) will ultimately require surgical drainage or resection [16,17], but most authors still advocate a first-line trial of PCD if technically possible. In a study of 25 patients with Crohn disease, PCD performed an average of 37 days before surgery significantly reduced the rate of severe, postoperative septic complications, such as anastomotic leak, intra-abdominal abscess, and fistula [18]. Published studies on the benefit of initial PCD to reduce the rate of postoperative septic complications demonstrate conflicting results, and the benefit of PCD for this purpose remains unclear [18,19].…”
Section: Discussion By Variantmentioning
confidence: 98%
“…In a study of 25 patients with Crohn disease, PCD performed an average of 37 days before surgery significantly reduced the rate of severe, postoperative septic complications, such as anastomotic leak, intra-abdominal abscess, and fistula [18]. Published studies on the benefit of initial PCD to reduce the rate of postoperative septic complications demonstrate conflicting results, and the benefit of PCD for this purpose remains unclear [18,19]. For mature abscesses associated with appendicitis, an initial combination of PCD, antibiotics, bowel rest, and (on occasion) hyperalimentation has been advocated for the same reason.…”
Section: Discussion By Variantmentioning
confidence: 98%
“…For ileocecal resections specifically, this complication rate increased from 7.2 to 40% [13]. In a retrospective cohort study, Müller-Wille et al [14] assessed whether percutaneous abscess drainage prior to surgery reduced the number of severe postoperative septic complications in patients with CD. It was shown that percutaneous drainage could significantly reduce the occurrence of severe intra-abdominal septic complications as compared to patients without percutaneous drainage (25 vs. 69%, p = 0.04).…”
Section: Combined Surgical Resection With Drainage or Percutaneous Drmentioning
confidence: 99%
“…Complications can vary from anastomotic leakage and abscesses to fistula formation. The overall risk of severe intra-abdominal septic complications, following bowel resection in CD patients, ranges between 9 and 13% [14]. The risk of intra-abdominal septic complications increases significantly in the presence of intra-abdominal abscesses at the time of surgery [15].…”
Section: Combined Surgical Resection With Drainage or Percutaneous Drmentioning
confidence: 99%